SME Performance: Ability to prepare financial reports based on SAK ETAP and financial literacy (Empirical study of SMEs in the city of Serang) - Puspita Maelani; Najmudin; Asep Yana Yusyama; Mohamad Husni (School of Industrial and System Engineering, Telkom University, 2024)
The background of this research is that SME managers in preparing financial reports based on SAKETAP, the managers are given training and assistance by the Department of Cooperatives, SMEs,Industry and Trade of Serang City, but the managers still focus on production without payingattention to recording financial transactions, thus hindering the managers in carrying outdevelopment, evaluation, and decision making. The formulation of the research problem is whetherthere is an influence between the ability to prepare financial reports based on SAK ETAP on theperformance of SMEs and financial literacy as a moderating variable. The aim of this research isto test and analyze whether there is an influence between the ability to prepare financial reportsbased on SAK ETAP on performance and financial literacy as a moderating variable. The researchmethod uses quantitative methods, the SMEs population in Serang City was taken using purposivesampling, hypothesis testing used PLS. The finding that the ability to prepare financial reportspossessed by managers in Serang City affects performance, this is due to the intensive training andmentoring carried out by the cooperative, SMEs, industry and trade services but SMEs managershave not been able to prepare it. general financial reports with financial literacy awareness. Thisresearch concludes that the ability to prepare financial reports and financial literacy have a positiveinfluence on SMEs performance, while the ability to prepare financial reports mediated byfinancial literacy has no effect on financial literacy.